MESIN PENETAS TELUR OTOMATIS BERBASIS MIKROKONTROLER ATMEGA 8535 DAN SENSOR SHT11 - Almido Haryanto Ginting; Samy Yeverson Doo; Aries Everd Leo (Universitas Nusa Cendana, 2017)
The hatching of eggs that has been done by manually and conventional still considered good and proper. But, in the hatch process, this conventional machine still need human help, which is for temperature control that still using human help to turn the light on or off, turning the eggs rack, controlling the fan and to open and close the door. All those things are doing to maintain hatching area still in good condition for hatching an egg to be successful. The purpose of this research is to design a prototype of an egg hatching machine that can work automatically based on microcontroller ATMega 8535 and SHT11 as temperature and humidity sensor. The result shows that SHT11 can work well to sense temperature and humidity so that the microcontroller can do its job whether open or close the door, turn off or turn on the light and so on in order to maintain the temperature and humidity as a key factor of hatching an egg.